2022
DOI: 10.3390/land11060839
|View full text |Cite
|
Sign up to set email alerts
|

Crop Production and Carbon Sequestration Potential of Grewia oppositifolia-Based Traditional Agroforestry Systems in Indian Himalayan Region

Abstract: Bhimal (Grewia oppositifolia) is the most important agroforestry tree species used for fodder, fuel and fiber in the Himalayan region. In the present study, G. oppositifolia-based traditional agroforestry systems were selected for the estimation of carbon stock and the production potential of barnyard millet (Echinochloa frumentacea) and finger millet (Eleusine coracana), with two elevational ranges, i.e., 1000–1400 and 1400–1800 m amsl, in Garhwal Himalaya, India. The results of the investigation showed a dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The traditional agroforestry system of the Garhwal Himalaya (Uttarakhand) is classified into various categories, i.e., agrosilviculture, agrohorticulture, and agrosilvohorticulture, and farmers cultivate different seasonal, biennial, and perennial crops, i.e., Echinochloa frumentaceae, Eleusine coracana, Triticum aestivum, Amaranthus spp., Vigna umbellata, and Oryza sativa, etc. Other associated species reported in these systems are Grewia optiva, Quercus leucotrichophora, Prunus cerasoides, Pyrus pasha, Ficus spp., etc., in the upper altitudes, and Toona ciliata, Melia azadirach, Bauhinia spp., Ficus spp., Grewia optiva, etc., in the lower altitude of agroforestry fields [19]. Seasonally, domestic animals use harvested fields for grazing.…”
Section: Study Site Characteristicsmentioning
confidence: 99%
“…The traditional agroforestry system of the Garhwal Himalaya (Uttarakhand) is classified into various categories, i.e., agrosilviculture, agrohorticulture, and agrosilvohorticulture, and farmers cultivate different seasonal, biennial, and perennial crops, i.e., Echinochloa frumentaceae, Eleusine coracana, Triticum aestivum, Amaranthus spp., Vigna umbellata, and Oryza sativa, etc. Other associated species reported in these systems are Grewia optiva, Quercus leucotrichophora, Prunus cerasoides, Pyrus pasha, Ficus spp., etc., in the upper altitudes, and Toona ciliata, Melia azadirach, Bauhinia spp., Ficus spp., Grewia optiva, etc., in the lower altitude of agroforestry fields [19]. Seasonally, domestic animals use harvested fields for grazing.…”
Section: Study Site Characteristicsmentioning
confidence: 99%
“…The relative microbiological potential of a sal forest, a bamboo crop, and a wetland may be inferred from their respective habitats. In a dry tropical forest in Rajasthan, India, Kumar et al found a significant amount of variation in the physicochemical makeup of the soil at various sites across the forest (Tariyal et al, 2022). The forest's varied soil textures and high chemical quality are thought to be responsible for this phenomenon.…”
Section: Soil Microbiological and Respiration Studiesmentioning
confidence: 99%
“…In India, more than 4,000 types of flowering plants are used for approximately 500 for fibres, 400 for fodder, 300 for gum, 3,000 for food, 700 for traditional religious and social usage and roughly 100 for medical purposes. Essential oils and perfumes are extracted from a range of species Thakur et al, 2017Thakur et al, , 2020Verma et al, 2017;Thakur et al, 2021b;Singh et al, 2021;Mansoori et al, 2020Mansoori et al, , 2022Sahoo et al, 2021;Tariyal et al, 2022). Thanks to India's rich biosphere, over a dozen novel chemicals and life-saving drugs have been found.…”
Section: Introductionmentioning
confidence: 99%